Analysis of Zhejiang Tea Culture in International Communication - Yang, Tongming; Zhang, Wenguo (International Journal of Social Sciences and Public Administration, 2025)
Zhejiang, a major tea-producing region in China, boasts a time-honored tea culture. Rich in philosophical ideas and artistic aesthetics, it stands as an outstanding representative of traditional Chinese culture. Amid globalization and frequent international cultural exchanges, Zhejiang tea culture has gone global. This thesis explores its origin, development, characteristics and role in international communication, outlines current status (e.g., active political, economic and folk exchanges), identifies existing problems, and proposes suggestions-such as policy-guided innovation and engaging Chinese and foreign youth-to let it shine worldwide, contributing to economic development, international friendship and cultural confidence.